HUMAN RIGHTS PARADIGMS IN ICSID INVESTMENT DISPUTE SETTLEMENT: A COMPARATIVE ASEAN STUDY - Enna Budiman (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
This research examines the dynamics of the relationship between the enforcement of Human Rights (HR) and the role of the International Centre for Settlement of Investment Disputes (ICSID) as the principal international arbitration institution in investment disputes. The background of this study is grounded in the tension between the protection of foreign investors—primarily through bilateral investment treaties—and the obligations of host states to safeguard public interests and the human rights of their citizens, which are often overlooked in conventional investment arbitration awards. The research raises two main questions: first, how human rights are positioned within ICSID jurisprudence; and second, how ASEAN countries integrate human rights clauses into their international investment agreements in order to balance economic and social interests. The research employs a normative juridical method, utilizing a conceptual approach, a statutory approach, and a comparative approach across several ASEAN member states. Secondary data in the form of ICSID arbitral awards and international investment agreements are analyzed qualitatively. The findings indicate that although ICSID has traditionally been investor–state centric, there is a discernible shift in which human rights issues are increasingly considered through state counter-claims. From a comparative perspective, several ASEAN countries have begun updating their model bilateral investment treaties to allow greater regulatory space for public policies related to human rights. In conclusion, harmonization between the international investment law regime and human rights law is crucial to prevent fragmentation in international law. This study recommends procedural reforms within the ICSID framework to accommodate third-party participation (amicus curiae) and the standardization of human rights clauses in investment treaties at the ASEAN regional level in order to strengthen the bargaining position of member states.